Mechanical Properties Evaluation of Cold-Curing Acrylic Resin Reinforced by Banana Peels’ Fibers. - Mohammed R. Gharkan; Ahmed H. Ali; Hossam E. Salman; Bassam I. Khalil (Diyala Journal of Engineering Sciences, 2019)
Although low mechanical properties of Acrylic resin, it is the most popular used substance as based denture materials. This drawback could be treated through adding reinforcing phase. In this work washing and non-washing banana peels as kind of natural fibers with different weight fractions, (5, 10, 15 and 20) % wt. and standared Acrylic, for compartion purpose, are used to prepare composite specimens by modeling method on order to study possibility of reinforcing cold-curing acrylic resin by banana peels. Peels had been dried, crashed, and washed by distillation water before using in the work. Unwashed peels also used for comparing purpose. Hardness, impact, and tendsile tests were performed to evaluate the development in mechanical properties of the prepared composite. Generally the results show that washed banana peels have more effective than that of un-washed peels, adding banana peels could improve hardness of composite and hardness increase with increasing weight fraction of peels till specific value, (10) % wt. where highest hardness recorded, using high weight fraction of reinforcing phase could negatively effect into mechanical properties of composite, Also the results show that using banana fibers as reinforce phase, didin’t improve impact strength, fracture toughness, and modules of elasticity properties of acrylic.